Experimental Investigation on Performance ByPass Cycle Multi-Split Cooling System-VRF - Arfidian Rachman; Nofriady Handra; Lisa Nesti (Jurnal Teknik Mesin, 2021)
Variable refrigerant flow air-conditioning (VRF) systems are important and widely used building energy systems around the world. In this study, the performance of a multi-split VRF system using the bypass cycle is evaluated using the experiment as a possible sub-cooling method to prevent flash gas generation in liquid pipelines. The experimental for the multi-split VRF system is developed by considering the applications of the bypass cycle, and is validated with experimental data. The results of the tests that have been carried out are obtained in the vapor compression cycle with a bypass cycle, an increase in cooling capacity of 2.96% and an energy saving ratio (EER) of 1.72%. The input power of the bypass cycle is reduced by up to 2.45% when the performance of the multi-split VRF systems with bypass cycle cooling capacity conditions.